Marganets bilan legirlangan kremniyda manfiy magnit qarshilik - Madjitov, M.X (SCIENCE and SOCIETY, 2023)
A large negative magnetoresistance phenomenon has been observed at room temperature by forming magnetic nanoclusters of manganese doped atoms in silicon by low-temperature diffusion. It has been shown that the negative magnetoresistance value can be controlled by controlling the concentration of manganese nanoclusters in silicon.
Keywords: silicon; magnetic semiconductor; manganese nanoclusters; magnetic resistance